New views of sport in Cuba: the emergence of football in the 21st century - Lisbona, Miguel (2018)
In less than two decades, soccer in Cuba has taken unprecedented prominence. However, the relevance that this sport has had has not been at a competitive level, much less infrastructure for its professional practice. It has functioned as a means of cultural expression, particularly of the new generations that, motivated by changes in telecommunications and the internet, and the openness towards tourism, have opted to look at football as a spectacle for consumption, instead of a professional sports practice. In this sense, our article proposes to see football, unlike what happens in the rest of the world, as an example of change in Cuba's cultural practices, taking as a reference the context of a country whose society seemed immutable to the transformations and offers of consumption, coming from the outside of the Island.